2020
DOI: 10.1002/ajpa.24198
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic and morphological variation in primate long bones reflects signals of size and behavior

Abstract: Objectives: Many primates change their locomotor behavior as they mature from infancy to adulthood. Here we investigate how long bone cross-sectional geometry in Pan, Gorilla, Pongo, Hylobatidae, and Macaca varies in shape and form over ontogeny, including whether specific diaphyseal cross sections exhibit signals of periosteal adaptation or canalization. Materials and methods: Diaphyseal cross sections were analyzed in an ontogenetic series across infant, juvenile, and adult subgroups. Three-dimensional laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 152 publications
(248 reference statements)
1
3
0
Order By: Relevance
“…Overall, these results are consistent with the prediction that ratios of Total.BV/TV between anatomical regions corresponds to agerelated variation in locomotor repertoire. These findings support evidence of strong associations between locomotor ontogeny and bone morphology from studies on midshaft diaphyseal cortical bone geometry (Pearson and Lieberman, 2004;Ruff et al, 2018;Nadell et al, 2021;Cosman, 2023). The relationship between trabecular bone ontogeny and age-related variation in locomotion is not as straightforward.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Overall, these results are consistent with the prediction that ratios of Total.BV/TV between anatomical regions corresponds to agerelated variation in locomotor repertoire. These findings support evidence of strong associations between locomotor ontogeny and bone morphology from studies on midshaft diaphyseal cortical bone geometry (Pearson and Lieberman, 2004;Ruff et al, 2018;Nadell et al, 2021;Cosman, 2023). The relationship between trabecular bone ontogeny and age-related variation in locomotion is not as straightforward.…”
Section: Discussionsupporting
confidence: 79%
“…Reconstructing age-related variation in locomotor behaviour from skeletal remains requires mechanically sensitive traits that are phenotypically plastic throughout ontogeny. Several studies have demonstrated the developmental plasticity in response to locomotor loading in hominoid long bone diaphyseal structure (Carrier, 1983;Cowgill, 2010;Cowgill et al, 2010;Sarringhaus et al, 2016;Cowgill and Robyn, 2018;Morimoto et al, 2018;Ruff et al, 2018;Nadell et al, 2021). Ruff and colleagues (2018) investigated the ontogeny of limb morphology and diaphyseal strength between relatively arboreal western lowland gorillas to more terrestrial Virunga mountain gorillas.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, African apes which have a locomotor repertoire that also involves parasagittal movements during knuckle‐walking, but whose arboreal locomotion is more important than in adult baboons, present even more mediolaterally oriented bending rigidity and thicker medial and lateral diaphyses (Morimoto et al, 2018; Nadell, 2017; Puymerail, 2011). Additionally, the mediolateral bending rigidity and strength that characterize the distal diaphysis of our adult sample, are observed in the femoral distal diaphysis of several primates with varied locomotor repertoire and body size including hominoids even in large bodied arboreal primates such as orangutans (Nadell et al, 2021; Rodríguez, 2018; Trinkaus & Ruff, 2012). Additionally, asymmetrical load resistance along the longitudinal axis of the diaphysis has been described in hominine (Mongle et al, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…This runs counter to the proposed direction of acclimation, including Weinstein's (2001) findings that warmer‐residing macaque species exhibit greater relative joint diameters than those in colder climates. Given the twofold decrease in female to male macaque body weight, it seems likely that female diaphyseal dimensions exhibited a relative increase either as an allometric constraint (Egi, 2001; Campione & Evans, 2012; Nadell et al, 2021) to facilitate stability or movement, rather than indications of physical activity (Lieberman et al, 2001; Ruff & Runestad, 1992), or locomotion preference (Godfrey et al, 1991).…”
Section: Discussionmentioning
confidence: 99%